2014
DOI: 10.1128/genomea.01257-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Pseudoalteromonas sp. Strain PLSV, an Ulvan-Degrading Bacterium

Abstract: We present the draft genome sequence of Pseudoalteromonas sp. strain PLSV, isolated from the feces of an Aplysia sea slug. The addition of the PLSV genome to the existing genomes of three other ulvan-degrading bacterial species will enhance our understanding of ulvan utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…52 Ulvan lyase activity has also been reported in Pseudoalteromonas spp. 53 This study confirms the ulvanolytic activity of bacteria belonging to genus Pseudoalteromonas. Further study on the ulvan lyases produced by the organism isolated in this study will help us determine if the enzyme is the same or diversity exists in the enzyme produced by different species from the same genus.…”
Section: Discussionsupporting
confidence: 78%
“…52 Ulvan lyase activity has also been reported in Pseudoalteromonas spp. 53 This study confirms the ulvanolytic activity of bacteria belonging to genus Pseudoalteromonas. Further study on the ulvan lyases produced by the organism isolated in this study will help us determine if the enzyme is the same or diversity exists in the enzyme produced by different species from the same genus.…”
Section: Discussionsupporting
confidence: 78%
“…LTR, and Pseudoalteromonas sp. PLSV, (8,12,13). Genome annotation was manually confirmed by CAZy 4 and revealed that these strains encoded many polysaccharide-degrading enzymes.…”
Section: Table 2 Primers Used In This Studymentioning
confidence: 99%
“…LTR, and Pseudoalteromonas sp. PLSV (12,13). Inspection of the genomes did not reveal genes encoding proteins homologous to N. ulvanivorans ulvan lyase.…”
mentioning
confidence: 96%
“…(10), and a Pseudoalteromonas sp. (11), will open up possibilities for the usefulness of polysaccharide ulvan from Ulva spp. Data availability.…”
mentioning
confidence: 99%